Improving Sensitivity and Specificity of Capturing and Detecting Targeted Cancer Cells with Anti-Biofouling Polymer Coated Magnetic Iron Oxide Nanoparticles - Lin, Run (Colloids Surf B Biointerfaces, 2016)
Detecting circulating tumor cells (CTCs) with high sensitivity and specificity is critical to management of metastatic cancers. Although immuno-magnetic technology for in vitro detection of CTCs has shown promising potential for clinical applications, the biofouling effect, i.e., non-specific adhesion of biomolecules and non-cancerous cells in complex biological samples to the surface of a device/probe, can reduce the sensitivity and specificity of cell detection. Reported herein is the application of anti-biofouling polyethylene glycol-block-allyl glycidyl ether copolymer (PEG-b-AGE) coated iron oxide nanoparticles (IONPs) to improve the separation of targeted tumor cells from aqueous phase in an external magnetic field. PEG-b-AGE coated IONPs conjugated with transferrin (Tf) exhibited significant anti-biofouling properties against non-specific protein adsorption and off-target cell uptake, thus substantially enhancing the ability to target and separate transferrin receptor (TfR) over-expressed D556 medulloblastoma cells. Tf conjugated PEG-b-AGE coated IONPs exhibited a high capture rate of targeted tumor cells (D556 medulloblastoma cell) in cell media (58.7 ± 6.4%) when separating 100 targeted tumor cells from 1×10(5) non-targeted cells and 41 targeted tumor cells from 100 D556 medulloblastoma cells spiked into 1 mL blood. It is demonstrated that developed nanoparticle has higher efficiency in capturing targeted cells than widely used micron-sized particles (i.e., Dynabeads(®)).